Rekonstruksi Qiwamah dalam Rumah Tangga Kontemporer: Analisis Fikih Keluarga Islam terhadap Dominasi Peran Istri dan Domestifikasi Peran Suami - Labib Ahmad Murtadho; Muhsan Syarafuddin (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Changes in social structure, rising economic participation of women, and the growing intellectual capacity of wives have produced the phenomena of wives' role dominance and husbands' domestification, reviving debates over the position of qiwamah in Islamic family law. This study analyzes the construction of qiwamah across the Hanafi, Maliki, Syafi'i, and Hanbali schools, examines the normative status of wives' role dominance and husbands' domestification, and explores whether fadl and financial maintenance function as the illah or merely the hikmah of qiwamah, along with their implications for contemporary Muslim family leadership. This qualitative library research uses a normative approach, drawing on classical fiqh texts across the four madhhabs, Qur'anic exegesis, scientific journals, and official statistical reports, analyzed through comparative, ushul fiqh, and socio-normative approaches. The findings show that all four madhhabs converge on understanding qiwamah as a mandate of leadership oriented toward responsibility, protection, and family welfare rather than male superiority, so a wife's economic dominance or intellectual superiority and a husband's greater domestic involvement do not automatically transfer qiwamah to the wife. Ushul fiqh analysis further shows that fadl and financial maintenance do not meet the criteria of a clear, fixed, and measurable illah, and are more appropriately positioned as the hikmah of qiwamah. This study concludes that changes in household role distribution affect only the implementation of rights and obligations, not the structure of family leadership, so the reconstruction of qiwamah should strengthen deliberation, cooperation, mutual good treatment, and shared responsibility in line with Islamic legal principles.